Maternal and neonatal characteristics of a Canadian urban cohort receiving treatment for opioid use disorder during pregnancy. (16th August 2018) - Miller, C.; Grynspan, D.; Gaudet, L.; Ferretti, E.; Lawrence, S.; Moretti, F.; Lafreniere, A.; McGee, A.; Lattuca, S.; Black, A.
Abstract: The epidemic of prescription and non-prescription opioid misuse is of particular importance in pregnancy. The Society of Obstetricians and Gynaecologists of Canada currently recommends opioid replacement therapy with methadone or buprenorphine for opioid-dependent women during pregnancy. This vulnerable segment of the population has been shown to be at increased risk of blood-borne infectious diseases, nutritional insecurity and stress. The objective of this study was to describe an urban cohort of pregnant women on opioid replacement therapy and to evaluate potential effects on the fetus. A retrospective chart review of all women on opioid replacement therapy and their infants who delivered at The Ottawa Hospital General and Civic campuses between January 1, 2013 and March 24, 2017 was conducted. Data were collected on maternal characteristics, pregnancy outcomes, neonatal outcomes and corresponding placental pathology. Maternal comorbidities identified included high rates of infection, tobacco use and illicit substance use, as well as increased rates of placental abruption compared with national averages. Compared with national baseline averages, the mean neonatal birth weight was low, and the incidence of small for gestational age infants and congenital anomalies was high. The incidence of NAS was comparable with estimates from other studies of similar cohorts. Findings support existing literature that calls for a comprehensive interdisciplinary risk reduction approach including dietary, social, domestic, psychological and other supports to care for opioid-dependent women in pregnancy.